Post-rectectomy choice of preventive intestinal stoma formation method: prospective multicenter randomized clinical trial protocol - P. V. Tsarkov; I. A. Tulina; P. B. Tsugulya; V. S. Kochetkov; S. V. Khmelik (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To justify and present the protocol of the prospective, multicenter randomized clinical trial for evaluation of the choice of preventive intestinal stoma formation method after rectectomy. Summary. Modern surgery for the rectal cancer is featured by preferential sphincter-preserving operations. It is established that colorectal anastomosis incompetence is severe and in some cases lethal complication that reduce quality of life of patients and an increase the risk of disease relapses, which rate reaches 15 to 20% at low colorectal anastomosis. Formation of preventive stoma is an effective way to avoid this complication that is why it’s inclusion to treatment protocols for the middle and low ampullary rectal cancers is undisputed by the most of surgeons. However the choice of preventive stoma formation method is under discussion yet and remains to be an urgent issue. In the western countries the preferred method is double barreled ileostomy due to more rapid formation and closure, as well as due to lower rate of stoma-related morbidity. In Russia and CIS countries application of double-barreled transverse colostoma is preferred traditionally due to lower rate of electrolytic disorders and related repetitive hospital admissions in conditions of imperfect stoma care system, along with series of unproven advantages, usually defined as hospital tradition. Conclusion. Presented study will allow to reveal the early and late postoperative morbidity rate and the related repeated hospital admissions in real-life clinical practice of Russia from the standpoints of evidencebased medicine, to define indications and contraindications for each method of «low» colorectal anastomosis protection with the least risk for the patient.